Developmental analysis of two wing scalloping mutants ct[6] and Bx[J] of Drosophila melanogaster. - Santamaria, P.; Garcia-Bellido, A. (Wilhelm Roux's archives of developmental biology, 1975)
The mutantscut (6) (ct(6)) andBeadex of Jollos (Bx (J)) show nicks in the wing margins as well as other malformations in different regions of the body. Clonal analysis of the wing disk's development in these mutants indicates that massive cell loss occurs during the third larval instar. Morphogenetic mosaics, originating from mitotic recombination, reveal a non-autonomous behaviour of both mutant and wild-type cells. X-rays applied during the third larval instar produce phenocopies of these mutants. A clonal and a genetic analysis of these phenocopies has been carried out.The hypothesis that scalloping mutants such asct (6), Bx(J) and others, as well as X-rays, affect properties of cellular interaction, such as cell adhesivity or cohesion, is discussed. Morphogenetic mosaics in the wing margin suggest that the differentiation of the marginal cuticular elements requires the interaction of the cells of the ventral and dorsal surfaces of the wing.